PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA DE RECAUDACIÓN Y PAGOS PARA EL CANTÓN PORTOVELO PROVINCIA DE EL ORO - Paladinez Caraguay, Guissella Carolina (2019)
The general objective of this thesis project is to determine the feasibility study for the creation of a collection and payment company for the families of the Portovelo province of El Oro, whose purpose is to satisfy the needs of the citizens, to offer the best services with security and trust and also guarantee the timely payment of their financial obligations and thereby raise the quality of life of the population. For the execution of the investigation, the deductive, inductive and statistical method was used, on the other hand, among the techniques the bibliographic, direct observation and survey was used that helped to compile the different opinions, attitudes and acceptance and reception that the company will have the population. In addition, a sample was taken which resulted in a total of 349 families who will be the subject of study. Regarding the results obtained through the market study, the unsatisfied supply and demand of the families was determined, as well as the reception of the company and the design of the marketing strategies that will be used in the execution of the same. In relation to the technical study, it was considered that the facilities will be located in the center of the city considering all the requirements and assurances necessary for the proper functioning, in order to provide good customer service. Regarding the administrative study, the structural organization chart and the manual of functions were established according to each work position; In the economic-financial study the investment, income, expenses, profitability and cash flow were estimated to later use the financial evaluation tools, where satisfactory results were obtained and from the financial point of view it is feasible the creation of the company collection and payments of the Portovelo cantón.